Validity of a Voice-Based Evaluation Method for Effectiveness of Behavioural Therapy - Shinohara, Shuji; Mitsuyoshi, Shunji; Nakamura, Mitsuteru; Omiya, Yasuhiro; Tsumatori, Gentaro; Tokuno, Shinichi (Pervasive Computing Paradigms for Mental Health, 2016)
In this study, we used General Health Questionnaire 30 (GHQ30) and voice to evaluate the stress reduction effect of a stress resilience program, and examined the validity of stress evaluation by voice. We divided the subjects who participated in the program into two groups by the number of training sessions. The results showed a stress-reduction effect only in the group with more training sessions (more than 13 sessions) for both GHQ30 and voice-based indexes. Moreover, both indexes showed a highly negative correlation between the pre-training value and the difference between the post-training and pre-training values. This implies that the effect of the training is more evident for subjects with higher stress levels. The voice-based evaluation showed trends similar to those displayed by GHQ30.